The Correlation Between Structure and Reading Comprehension Achievement of the Students : Case Study SMP Swasta Budi Insani Medan - Naetty Siahaan; Tambun Sihotang; Sondang Mariana Silalahi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2021)
This study was intended to find out the correlation between structure and reading comprehension achievement of the third year students of SMP Swasta Budi Insani Medan. There were 30 students out of 115 randomly selected as the sample. The data was collected by giving multiple choce test that consisting 50 items for structure test and 30 items for reading comprehension test. The data were analyzed by applying Pearson’s Product Moment Formula. The finding shows that r was 0,738. It means that, there is the possitive effect between structure and reading comprehension. This implies the more students know about the knowledge of structure, the better understanding the students will be added the reading compreheension. These proved to be greater than the critical value of r at the level of 0,05 which is 0,361. Based on the data which have been found in this study, it can be concluded that there is a significant correlation between the students structure and reading comprehension achievement.